Building technological capability : issues and prospects : Nepal, Bangladesh and India - Huq, M. M. (Dhaka : University Press, 2003)
Contributed articles.
Includes bibliographical references and index.
Keywords: Technological innovations -- Developing countries; Research, Industrial -- Developing countries; Technical assistance -- Developing countries